Concurrent granulomatous Pneumocystis carinii and Mycobacterium xenopi pneumonia: an unusual manifestation of HIV immune reconstitution disease. Issue 11 (29th October 2004) - Chen, F; Sethi, G; Goldin, R; Wright, A R; Lacey, C J
Abstract : This report of concurrent granulomatous Pneumocystis carinii pneumonia (GPCP) and Mycobacterium xenopi pneumonia (MXIP) in a patient with advanced HIV disease 3–5 weeks after commencing antiretroviral therapy (ART) fits the syndrome of HIV immune reconstitution/restoration disease (IRD). It may also be a unique window into the immunology of granulomatous inflammation.